2023
DOI: 10.1038/s41587-022-01593-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-time, volumetric imaging of radiation dose delivery deep into the liver during cancer treatment

Abstract: Ionizing radiation acoustic imaging (iRAI) allows online monitoring of radiation’s interactions with tissues during radiation therapy, providing real-time, adaptive feedback for cancer treatments. We describe an iRAI volumetric imaging system that enables mapping of the three-dimensional (3D) radiation dose distribution in a complex clinical radiotherapy treatment. The method relies on a two-dimensional matrix array transducer and a matching multi-channel preamplifier board. The feasibility of imaging temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…In our previous study, simulations were completed to account for these effects 50 . For patient study feasibility, X. Wang and I. El Naqa's group demonstrated that with LINAC x‐ray beam, relative dose distribution field can be reconstructed 51 . However, they pointed out that their methods mostly image the edges of the radiation field, and better algorithms are needed to get quantitative dose information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, simulations were completed to account for these effects 50 . For patient study feasibility, X. Wang and I. El Naqa's group demonstrated that with LINAC x‐ray beam, relative dose distribution field can be reconstructed 51 . However, they pointed out that their methods mostly image the edges of the radiation field, and better algorithms are needed to get quantitative dose information.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, implementing a transducer array can improve the SNR. In Zhang et al., 51 they achieved high SNR signals in liver with a planar transducer array that has center frequency of 0.35 MHz. Hence, we will be able to reconstruct dose more accurately in deeper fields by improving SNR.…”
Section: Discussionmentioning
confidence: 99%
“…A clinically ready iRAI imaging system was adapted from our previous commercial US platform based iRAI and US dual-modality imaging system 14,17 , shown in Fig. 1A.…”
Section: Methodsmentioning
confidence: 99%
“…In continuous and repeatable cancer treatment modalities including PDT and hyperthermia, monitoring cancer progression concurrently with treatment is important to evaluate and improve treatment effectiveness. This is typically done through regular imaging studies 24,25 , such as computed tomography (CT) scans, or bioluminescence. These tests help to determine the size and spread of cancer and can help guide decisions about treatment options and adjustments.…”
Section: Introductionmentioning
confidence: 99%